PUBERTAL DEVELOPMENT OF TURKISH BOYS IN ELAZIG, EASTERN TURKEY - YENIOGLU, H; GUVENC, H; AYGUN, AD; KOCABAY, K (Taylor & Francis Ltd London, 1995)
Data on pubertal development in 462 healthy, well-developed schoolboys from the cross-sectional study in Elazig, Eastern Turkey, are reported. Genital and pubic hair development are classified according to Marshall and Tanner, and Winter criteria. The initiation of genital development (the onset of puberty) was 11.6 +/- 0.15 (mean +/- SEM) years and that of pubic hair development was 12.2 +/- 0.16 years. The completion of genital and pubic hair development occurred at the same age, namely at 15.7 +/- 0.11 years. On average the genitalia and pubic hair reached the adult stage 4.2 and 3.6 years after they began to develop, respectively. As a general comment Eastern Turkish boys' pubertal data are in good agreement with English, North American and South African data.
Keywords: Children; Ankara